Development and validation of a multi‐analyte LC‐MS/MS approach for quantification of neuroleptics in whole blood, plasma, and serum. Issue 10 (25th November 2015) - Montenarh, Deborah; Hopf, Markus; Maurer, Hans H.; Schmidt, Peter; Ewald, Andreas H.
Abstract : Based on a similar approach for quantification of antidepressants, benzodiazepines, and z‐drugs, a liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) multi‐analyte approach with simple liquid‐liquid extraction was extended for fast target screening and quantification of neuroleptics in whole blood, plasma, and serum. As this method is part of a multi‐analyte procedure for over 100 analytes from different drug classes and as the extracts were additionally used in the authors' laboratory for gas chromatography‐mass spectrometry (GC‐MS) analysis, one universal stable‐isotope‐labelled internal standard (SIL‐IS) was used to save time and resource. The method was validated with respect to international guidelines. For accuracy and precision, full calibration was performed with ranges from subtherapeutic to toxic concentrations. Selectivity problems could not be observed, but matrix effects ranged from 68 to 211% in all samples. For the low quality control (QC), recovery ranged from 32 to 112%, process efficiency from 31 to 165% and for the high QC recovery from 42 to 141%, process efficiency from 29 to 154%. In addition statistical data evaluation of the variances of the recovery, matrix effects, and process efficiency data between whole blood vs. plasma, whole blood vs. serum, and plasma vs. serum were done. The presented LC‐MS/MS approach was applicable for selective detection of 33 neuroleptics as well as accurate and precise quantification of 25 neuroleptics in whole blood, 19 in plasma, and 17 in serum. More significant matrix effects (ME) for neuropletic drugs overall in plasma and serum as compared with whole blood were detected. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A method for quantification of neuroleptics in serum, plasma, or whole blood embedded in general multi analyte approach for benzodiazepines, antidepressants, and neuroleptics using LC‐MS/MS is presented.